Cloud Communication Based Avionics - R, Sam Jose (International Journal of Students' Research in Technology & Management, 2015)
This technology involves introduction of cloud computing technology inside aircraft for multiplexing data and transfer the multiplexed signal to a communication satellite where demultiplexing of data takes place. These data are then sent to various corresponding transmission towers and the response signal reaches the satellite from these transmission towers where multiplexing of various signals is done. Now the multiplexed signal is again sent to cloud inside aircraft thus making communication possible without any vulnerability or distortion.